(untitled) (Zien Journal of Social Sciences and Humanities, 2026)
In this article, the processes of settlement of Kyrgyz tribes in the territory of Uzbekistan, as well as the dynamics of their numerical growth from the end of the 19th to the beginning of the 21st century, have been scientifically analyzed.